2019
DOI: 10.1371/journal.pone.0216931
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status of reproductive age women and their toddlers in northern Ghana improved through household supply of iodized salt and weekly indigenous meal consumption

Abstract: Iodine deficiency (ID) during pregnancy results in pregnancy losses, intrauterine growth retardation, and lower IQ in the offspring. Even after two decades of universal salt iodization (USI) implementation, the efficacy of USI has not been reported in high risk groups in vulnerable regions in Ghana. We aimed to assess and improve ID status in childbearing age women (all lactating women) and their toddlers in northern Ghana, a geographically and socioeconomically vulnerable region. We provided weekly supply of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Based on the monotony of the diet, one 24-h recall is enough to approximate routine or usual food intake in this setting. The non-significant findings in toddlers may be due to consumption of breast milk as their source of nutrients (15,25) . In this study, two DP were identified for women (DP 1 and DP 2) and one DP (DP 2) for toddlers.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Based on the monotony of the diet, one 24-h recall is enough to approximate routine or usual food intake in this setting. The non-significant findings in toddlers may be due to consumption of breast milk as their source of nutrients (15,25) . In this study, two DP were identified for women (DP 1 and DP 2) and one DP (DP 2) for toddlers.…”
Section: Discussionmentioning
confidence: 98%
“…Optimal design software (version 3.01) was used to calculate the minimal adequate sample size of 100 dyads with a power of 80 %, significance level of 5 %, coefficient of determination of 65 %, minimum detectable effect of 0•33 of diet on Fe and iodine status and 20 % attrition rate. Details of research methods and recruitment have been published earlier (15,25) . Data analyses were carried out using SAS 9.4 (SAS Institute Inc.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations